It's a Situationship: How Online Contingent Faculty Talk About Their Needed Support - Yvonne Earnshaw; Mary Ann Bodine Al-Sharif (Online Learning)
This study used critical discourse analysis to examine how contingent faculty teaching in online programs talk about the support they need. We interviewed 10 online contingent faculty in the United States. Our findings suggest that our participants are off the radar and not included, their contingent role is a perceived gateway and is one of convenience for both the contingent faculty and the institution, and there is an imbalance of power. Online contingent faculty need to feel more included in the communication from the program or department and need to have more pedagogical and technical support. Additionally, they need more information to help support their students and professional development for themselves.